An Integrated Optical-Electrical Modelling Framework and Fabrication Techniques for Large-Scale Luminescent Solar Concentrator Modules - Glenn, Aaron Crommer (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2025)
The European Union aims to achieve at least a 55% reduction in greenhouse gas emissions by 2030, en route to reaching climate neutrality by 2050, as outlined in the European Green Deal. Achieving these ambitious targets requires the development of advanced, cost-effective, and environmentally sustainable energy technologies. Solar energy, abundant and low in carbon footprint, is central to this transition, but existing photovoltaic (PV) systems face challenges in scaling, integration, and efficiency. This thesis addresses these challenges by advancing the modelling, fabrication, optimisation, and performance evaluation of luminescent solar concentrators (LSCs) and their plasmonically enhanced counterparts (PLSCs) to improve solar energy harvesting efficiency and adaptability. To begin, a thorough review of global energy challenges and photovoltaic technologies identifies the need for cost-effective, sustainable solutions that can integrate seamlessly into buildings and infrastructures. LSCs and PLSCs, capable of harvesting diffuse and direct sunlight, emerge as promising approaches due to their flexibility, low-carbon footprint, and architectural versatility. A core contribution of this work is the development and validation of a comprehensive optical and electrical simulation framework, the PEDAL/Plasmon/Evolute model, which integrates Monte Carlo ray tracing and Finite-Difference Time-Domain methods to capture complex optical interactions, including plasmonic effects introduced by metal nanoparticles (MNPs). This integrated model accurately predicts device outputs under varying solar radiation conditions, providing a powerful tool for optimising dye and metal nanoparticle concentrations, as well as the device configuration. The novel validated electrical model can accurately predict the power output and power conversion efficiencies of LSC devices using area-specific solar radiation data as the only experimental measurement required. A comprehensive model-optimised LSC fabricated via a novel integrated stay-in-mould fabrication methodology has been developed which ensures reproducible device quality and simplifies scaling from individual LSC units to larger, modular panel installations. Incorporating PV cells within the host matrix improves structural integrity and optical coupling. Laboratory and outdoor experiments confirm the models predictions that a lumogen red dye concentration of 70 ppm and the inclusion of reflectors is optimal, while integrating plasmonic nanoparticles significantly enhances the power output and power conversion efficiencies further. Real-world testing of a 1 m^2 panel demonstrates consistent performance improvements, validating the scalability and architectural compatibility of these technologies. Under outdoor conditions, plasmonically enhanced LSC devices achieved power conversion efficiencies exceeding 3%, nearly double that of standard LSCs, and displayed robust stability under fluctuating solar irradiance. Incorporating reflective backings improved device power outputs by approximately 25%. Initial exploration of 3D resin printing suggests opportunities for custom, more complex geometries and specialised designs, although further optimisation of material properties is needed. The thesis highlights the critical parameters influencing device efficiency and long-term stability by comparing standard LSCs, PLSCs, and reference devices under controlled indoor and dynamic outdoor conditions. In summary, this research offers a validated simulation framework, reproducible fabrication strategies, and practical performance data - all of which lay a solid foundation for next-generation LSC and PLSC systems. The outcomes chart a clear path from lab-scale prototypes to commercially viable, higher-efficiency solar energy solutions more suitable for practical, real-world applications.
APPROVED
Keywords: Metal Nanoparticles; Localised Surface Plasmon Resonance (LSPR); Modular LSC Panel Integration; 3D Printing; Building-Integrated Photovoltaics (BIPV); Outdoor Performance Validation; Dye Concentration & Spectral Tuning; Luminescent Solar Concentrator (LSC); Plasmonic Luminescent Solar Concentrator (PLSC); Integrated Optical-Electrical Modelling; Monte-Carlo Ray Tracing (MCRT); Finite-Difference Time-Domain (FDTD)